Cheating prevention visual cryptography scheme using Latin square. (1st July 2017) - Ren, Yawei; Liu, Feng; Guo, Teng; Feng, Rongquan; Lin, Dongdai
Abstract : In the past decade, the researchers paid more attention to the cheating problem in visual cryptography (VC) so that many cheating prevention visual cryptography schemes (CPVCS) have been proposed. In this paper, the authors propose a novel method, which first makes use of Latin square to prevent cheating in VC. Latin squares are utilised to guide the choosing of authentication regions in different rows and columns of each divided block of the shares, which ensures that the choosing of authentication regions is both random and uniform. Without pixel expansion, the new method provides random regions authentication in each divided block of all shares. What is important is that the proposed method is applicable to both ( k, n )‐deterministic visual cryptography scheme (( k, n )‐DVCS) and ( k, n )‐probabilistic visual cryptography scheme (( k, n )‐PVCS). Experimental results and properties analysis are given to show the effectiveness of the proposed method.